2020
DOI: 10.1080/13603124.2020.1744734
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing school leadership: from psychology to philosophy

Abstract: Arguably the notion of the school leader as the all-important person in school improvement in England still holds sway, despite the development of a huge range of leadership theories and perspectives which suggest a broader contextual approach may be appropriate. Reflecting on the development of a MA course in leadership and management, this paper argues that a philosophical approach based on the later work of Wittgenstein is helpful. The starting point for the approach used here is Wittgenstein's notion of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies show that many factors affect school improvement, of which leadership is the most important (Newman, 2020). Other important factors are teacher professional improvement and the school’s transformation into a learning organization (Jacobs & Struyf, 2015; Senge, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies show that many factors affect school improvement, of which leadership is the most important (Newman, 2020). Other important factors are teacher professional improvement and the school’s transformation into a learning organization (Jacobs & Struyf, 2015; Senge, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we determined 5 basic factors by focusing on the variables revealed during previous studies. These factors are effective leadership, school climate, teacher professional development, learning environment, vision, and mission (Lee & Louis, 2019; Newman, 2020; Prenger et al, 2021). The minimum and maximum score obtainable from the developed scale is 33, and 165, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, leadership is synonymous with the process of management, including mindsets and skills taken from businessbased thinking. This thinking is often associated with a managerial skillset highlighted by step-bystep planning and mistake-free solutions (James et al, 2020;Newman, 2020).…”
Section: The Leadership Lens In Higher Educationmentioning
confidence: 99%
“…Inspirational leadership (followers feel valued; and finally, there is the idealized influence related to the charism, which arises from an identification emotional among the group leader and his associates); 4. Idealized influence [17]. Pedagogical leadership.…”
Section: Literature Reviewmentioning
confidence: 99%